Implementation of OFDM wireless communication model for achieving the improved BER using DWT-OFDM (International Journal of Engineering and Computer Science, 2017)
Orthogonal Frequency Division Multiplexing (OFDM) is of the strong prospects as a future wireless communication system. OFDM is one of the key technologies which enable non-line of sight wireless services making it possible to extend wireless access method over wide-areas. Multicarrier modulation is such a plan, to the point that transmits the information by isolating the serial high information rate streams into various low information rate parallel information streams. Orthogonal Frequency Division Multiplexing (OFDM) is a sort of multi-transporter balance, which partitions the accessible range into various parallel subcarriers and each subcarrier is then adjusted by a low rate information stream at various carrier frequency. Compared to conventional approaches the 4th generation Long term evolution application has better spectral efficiency in terms of accuracy and high data rate, the 4th generation Long term evolution approach is formed by the collaboration of OFDM and MIMO. Although OFDM has many advantages over FDM but it suffers from inter carrier interference and inter symbol interference when multiple carriers are used and due to this interferences loss of Orthogonality happens, in order to overcome these interferences usage of cyclic prefix has became mandatory. But usage of cyclic prefix shows huge negative impact on bandwidth efficiency as the cyclic prefix approach consumes nearly 20% of bandwidth and BER performance too affected. In this paper a novel wavelet based OFDM model is presented which is mainly intended to provide good Orthogonality and better spectral efficiency using various modulation techniques, the unique thing in the usage of wavelet based OFDM is it does not need any spectral efficiency and absence of the cyclic prefix increases bandwidth efficiency when bandwidth increases simultaneously spectral efficiency increases. Finally the usage of the wavelet based OFDM shows improved BER over conventional FDM communication model. The simulation results indicates the usage of wavelet based OFDM in place of DWT based OFDM in LTE and finally the comparison between wavelet based OFDM and DFT based OFDM